Forecasting of Lithuanian Industry, Construction, Agriculture Development and Their Demand for the Fuel and Energy Resources: the Methodical Principles and Forecasts Till Year 2000 - Balsys, Ovidijus; Mačiekus, Venantas (Ekonomika, 1995)
The rise in prices of the fuel and energy resources to the world market level will manifest itself as a structural changes that will take place till the year 1994 with both the production decline and the energy consumption decrease in the background. In this article these changes are estimated as depending on the output and fuel-energy consumption elasticity for fuel-energy prices.The industrial constructional and agricultural growth is expected to start arround the 1995–1996 and by the year 2000 the production level is forecasted to reach approximately 75% of the 1990 year level (in comparative prices). The most optimistic forecast is for Light Industry (118% of the 1990 year level).By the year 2000 the fuel and energy consumption is expected to decrease approximately to 40% of the 1990 year level. This bigger decline, compared with output decrease, is closely related to the smaller intensity of energy use.